2016
DOI: 10.1177/0885328216638636
|View full text |Cite
|
Sign up to set email alerts
|

Improving PEEK bioactivity for craniofacial reconstruction using a 3D printed scaffold embedded with mesenchymal stem cells

Abstract: This study demonstrates for the first time that SLS 3D printing can be used to fabricate customized porous PEEK scaffolds that maintain the viability of adipose and bone marrow-derived MSCs and induce the osteodifferentiation of the adipose-derived MSCs. The combination of 3D printed PEEK scaffolds with MSCs could overcome some of the limitations using PEEK biopolymers for load-bearing bone regeneration in craniofacial reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 29 publications
1
78
0
1
Order By: Relevance
“…Initial reports of bone ingrowth into porous PEEK implants supported this view, yet, until now, porous PEEK technologies in the literature had yet to reach clinical use and remained at various stages of development (Table 1) 13,3239 . Herein, we describe a new porous PEEK biomaterial with similar physical and mechanical properties of standard PEEK that is able to osseointegrate without the typical fibrous tissue response associated with current smooth PEEK implants.…”
Section: Introductionmentioning
confidence: 99%
“…Initial reports of bone ingrowth into porous PEEK implants supported this view, yet, until now, porous PEEK technologies in the literature had yet to reach clinical use and remained at various stages of development (Table 1) 13,3239 . Herein, we describe a new porous PEEK biomaterial with similar physical and mechanical properties of standard PEEK that is able to osseointegrate without the typical fibrous tissue response associated with current smooth PEEK implants.…”
Section: Introductionmentioning
confidence: 99%
“…Roskies et al demonstrated that porous polyetheretherketone (PEEK) scaffold can be prepared using SLS technology, which is capable of maintain the biological activity of cells and is conducive to the differentiation of osteoblasts [45].…”
Section: Selective Laser Sinteringmentioning
confidence: 99%
“…SLS can also be used to produce polyetheretherketone (PEEK) scaffolds that are widely applied in orthopedic surgery. Roskies et al (2016) used SLS to fabricate customized porous PEEK scaffolds for seeding mesenchymal stem cells (MSCs) to enhance osteodifferentiation.…”
Section: Selective Laser Sinteringmentioning
confidence: 99%